AAV-Containing Exosomes as a Novel Vector for Improved Gene Delivery to Lung Cancer Cells - Liu, Bin; Li, Zhiqing; Huang, Shi; Yan, Biying; He, Shan; Chen, Fengyuan; Liang, Yaxuan (Frontiers in Cell and Developmental Biology, 2021)
Lung carcinoma is the most common type of cancer and the leading cause of cancer-related death worldwide. Among the numerous therapeutic strategies for the treatment of lung cancer, adeno-associated virus (AAV)-mediated gene transfer has been demonstrated to have the potential to effectively suppress tumor growth or reverse the progression of the disease in a number of pre-clinical studies. AAV vector has a safety profile, however, the relatively low delivery efficacy to particular subtypes of lung carcinoma has limited its prospective clinical translation. Exosomes are nano-sized extracellular vesicles secreted from nearly all known cell types. Exosomes have a membrane-enclosed structure carrying a range of cargo molecules for efficient intercellular transfer of functional entities, thus are considered as a superior vector for drug delivery. In the present study, we developed a novel strategy to produce and purify AAV-containing exosomes (AAVExo) from AAV-packaging HEK 293T cells. The cellular uptake capacity of exosomes assisted and enhanced AAV entry into cells, and protected AAV from antibody neutralization, which was a serious challenge for AAV in vivo application. We tested a list of lung cancer cell lines representing non-small-cell lung cancer and small-cell lung cancer, and found that AAVExo apparently improved the gene transfer efficiency compared to conventional AAV vector. Our in vitro results were supported in vivo in a lung cancer xenograft rodent model. Additionally, we evaluated the gene delivery efficiency in the presence of neutralizing antibody on lung cancer cells. The results demonstrated that AAVExo-mediated gene transfer was not impacted, while the AAV vectors were significantly blocked by the neutralizing antibody. Taken together, we established an efficient methodology for AAVExo purification, and the purified AAVExo largely enhanced gene delivery to lung cancer cells with remarkable resistance to antibody neutralization.